Genetic variability, correlation and path analysis for yield and its component traits in restorer lines of rice (Bangladesh Journal of Agricultural Research, 2019)
Twenty nine restorer lines of rice were evaluated for fourteen agro-morphological traits during Boro (irrigated rice) season of 2012-2013 at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur, and Bangladesh. Analysis of variance revealed significant differences among the restorer lines for all the traits studied.The phenotypic coefficient of variation (PCV) was higher than genotypic coefficient of variation (GCV) for all the traits indicating the presence of little environmental influence in the phenotypic expression. Heritability estimate was found high for all the yield contributing traits. High heritability along with high genetic advance as per cent of mean was recorded for secondary branches per panicle followed by number of effective tillers, flag leaf area and panicle weight. Contrary, days to flowering and days to maturity showed high heritability coupled with low genetic advance as per cent of mean. Pearson correlation revealed grain yield had positive association with number of effective tillers per hill, panicle length, spikelet fertility, flag leaf area, plant height and thousand grain weights. Mentioned characters also found positive association with yield in both genotypic and phenotypic level. Spikelet fertility, number of secondary branches per panicle, thousand grain weights and number of effective tiller possessed higher positive direct effect on grain yield. It indicated the importance of these traits as selection criteria of yield improvement in hybrid rice programme.Bangladesh J. Agril. Res. 44(2): 291-301, June 2019